Features of the Energy Spectrum of Cosmic Rays above 2.5×10^{18} eV Using the Pierre Auger Observatory - Aab, A; Abreu, P; Aglietta, M; Albury, J M; Allekotte, I; Almela, A; Alvarez Castillo, J; Alvarez-Muñiz, J; Alves Batista, R; Anastasi, G A; Anchordoqui, L; Andrada, B; et al. (Physical review letters, 2020)
We report a measurement of the energy spectrum of cosmic rays above 2.5×10^{18} eV based on 215 030 events. New results are presented: at about 1.3×10^{19} eV, the spectral index changes from 2.51±0.03(stat)±0.05(syst) to 3.05±0.05(stat)±0.10(syst), evolving to 5.1±0.3(stat)±0.1(syst) beyond 5×10^{19} eV, while no significant dependence of spectral features on the declination is seen in the accessible range. These features of the spectrum can be reproduced in models with energy-dependent mass composition. The energy density in cosmic rays above 5×10^{18} eV is [5.66±0.03(stat)±1.40(syst)]×10^{53} erg Mpc^{-3}.